Predictive diagnostic and/ or prognostic biomarkers obtained from routine blood biochemistry in patients with solitary intracranial tumor - Yuksel, Ulas (Journal of Medical Biochemistry, 2020)
Background: Radiological and/or laboratory tests may be sometimes inadequate to differentiate glioblastoma from metastatic brain tumors. This study aimed to find biomarkers that distinguish between glioblastoma and metastatic brain tumor by using blood biochemistry analysis results evaluated preoperatively in patient with solitary intracranial tumor. Methods: Patients admitted to neurosurgery clinic between January 2015 and September 2018 were included in this study and they were divided into two groups called GLIOMA (n=12) and METASTASIS (n=17). Patients’ data consisted of age, gender, Glasgow Coma Scale scores, length of stay in hospital, Glasgow Outcome Scale (GOS) scores and histopathological examination reports was recorded. Hemoglobin level, count results of the leukocyte, neutrophil, lymphocyte, monocyte, eosiophil, basophil and platelet, neutrophil-lymphocyte ratio and platelet-lymphocyte ratio results, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) levels were evaluated preoperatively. Results: The CRP levels of METASTASIS group (14.31±2697) were significantly higher than those of GLIOMA group (2.39±4.99). CRP was 82% sensitive and 75% specific in distinguishing the metastatic brain tumor from glioblastoma if CRP level value was >5.5 mg/dL. A positive correlation was determined between GOS score and hemoglobin level and between ESR and CRP values. A negative correlation was found between GOS score and ESR level and between GOS score and duration of hospitalization. Conclusion: It was considered that CRP level values could be a predictive biomarker in distinguishing metastatic brain tumor from glioblastoma; and ESR, CRP, hemoglobin levels and duration of hospital stay could be prognostic biomarkers in predicting short-term prognosis of patients with intracranial tumor.